Perancangan Dan Implementasi Aplikasi Penunjang Dalam Melakukan Audit (Studi Kasus Uin Syarif Hidayatullah Jakarta) - Mezan el-Khaeri Kesuma; Fadhilah Mathar; Fenty Eka Muzayyana Agustin; Wilda Farah; Muhamad Brilliant; Tiara Widi Astuti (Jurnal Sistem Informasi, 2022)
Nowadays, various government agencies/institutions have realized how important the role of information technology is in getting data and information from around the world quickly, precisely and accurately.  One of them is in supporting and assisting in the efforts of Auditing the Management of State Financial Responsibilities.  The State Islamic University (UIN) Syarif Hidayatullah carries out its routine activities, namely conducting State Finance Inspections, Planning and Accountability (Audits) starting from SPI (Intern Auditor) to the Inspectorate General (Itjend) Ministry of Religion (Kemenag) and the Financial Supervisory Agency (BPK), here the researchers provide solutions that is, one way is to use a Supporting Application in conducting an audit. The purpose of this application is to increase efficiency, effectiveness, and transparency in the Audit of State Finance Accountability Management because this is one of the characteristics of Good Government / Good Cooperate Government.  The results of this study: (1) can facilitate the activities of the Audit and Management and Accountability of State Finances;  (2) preventing the occurrence of fraudulent KKN (Corruption practices;  (3) the existing funds are also expected to improve student services at UIN Jakarta.